(untitled) (Bangladesh Journal of Medical Education, 2022)
The modern concept of a curriculum originally derived from the Latin word for a race course. Undergraduate medical education is part of a continuum of education and training.The new curriculum is structured to provide a balance among learning opportunities through integrated teaching system. This study was carried out to explore the views of teachers and students regarding the current undergraduate medical curriculum. This cross-sectional descriptive study was conducted between October 2019 to October 2020 among the teachers and students of a private medical college and hospital (MH Samorita medical collegesandhospital) in Dhaka Bangladesh. The sample size were 100 in total. Most of the participants suggested for changes in overall existing MBBS curriculum. Highest satisfaction was seen in content related to learning objectives that were 90% and highest dissatisfaction was seen in Phase distribution of subjects that were 89%.However, they were satisfied with present pattern of course content, objectives, evaluation system and carry on system. Teachers and students evaluation may prove useful if analyzed further to overcome the shortcomings of existing MBBS curriculum. Bangladesh Journal of Medical Education Vol.13(1) January 2022: 27-32